Implementasi Metode Waterfall Pada Perancangan Website Company Profile Untuk Biro Jasa Lina Bugis (Studi Kasus : Biro Jasa Lina Bugis) - Sahroni; Muhammad Fahri, Syaiful; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
In the digital era, technological adaptation has become essential for companies to enhance their competitiveness in an increasingly dynamic market. This study aims to design and implement a company profile website for Lina Bugis Agency using the Waterfall software development method. The methodology is applied through several stages: requirement analysis, design, implementation, testing, and maintenance. The website is designed to address the limitations of traditional promotional methods used by Lina Bugis Agency, such as brochures and word-of-mouth communication. The result of this study is a website that provides comprehensive information about the services offered, including vehicle registration renewal (STNK), tax payment, and document management. The website is equipped with interactive features such as a comment form, location maps, and WhatsApp integration to facilitate communication with customers. This system is expected to improve the agency's promotional effectiveness, broaden market reach, and provide more responsive services to its clients.